Lactobacillus gasseri LGV03-derived indole-3-lactic acid ameliorates immune response by activating aryl hydrocarbon receptor - Zikang Zhang; Kangdi Zheng; Zhao Zhang; Longbin Cao; Lizhu Lin; Weimin Sun; Feng Qiu (Microbial Cell Factories)
Abstract Previous studies showed that the female genital tract microbiome plays a crucial role in regulating the host’s immune defense mechanisms. Our previous research has shown that Lactobacillus gasseri LGV03 (L. gasseri LGV03) isolated from cervico-vagina of HPV-cleared women contributes to clearance of HPV infection and beneficially regulate immune response. However, the mechanisms behind the regulation of L. gasseri LGV03 in immune response remain unclear. To better understand the interaction between female genital tract microbiome and immune function, the immunomodulatory activities of L. gasseri LGV03 were investigated in zebrafish models of neutropenia, macrophage and T cells deficiency. L. gasseri LGV03 showed higher potent activities in ameliorating vinorelbine-induced neutropenia, macrophage and T cells deficiency, and significantly enhanced mRNA expressions of cytokines TNF-α, TNF-β and IFN-α. Moreover, the transcriptome sequencing results indicated L. gasseri LGV03 might alleviate vinorelbine-induced immunosuppression in zebrafish. Non-targeted detection and analysis revealed that indole derivatives including phenylacetaldehyde, 3-phenyllactic acid, N-acetylserotonin and indole-3-lactic acid were significantly increased in the lysate and supernatant of L. gasseri LGV03. Meanwhile, L. gasseri LGV03 supernatant and indole-3-lactic acid ameliorated the vinorelbine-induced reduction in abundance of macrophages, neutrophils and T cells. However, the alleviating effects of L. gasseri LGV03 supernatant or indole-3-lactic acid were eliminated by aryl hydrocarbon receptor (AHR) antagonist CH-223,191. Furthermore, L. gasseri LGV03 supernatant and indole-3-lactic acid significantly increased the secretion of IFN-α, IFN-β and chemokines (MIP-1α, MIP-1β) in Ect1/E6E7 cells, meanwhile, these benefits were eliminated by CH-223,191 treatment. In summary, L. gasseri LGV03-derived indole-3-lactic acid can activate AHR-mediated immune response.